Psychotropic drug prescription rates in primary care for people with dementia from recorded diagnosis onwards. (16th October 2020) - Joling, Karlijn J.; Koppel, Maud ten; van Hout, Hein P.J.; Onwuteaka‐Philipsen, Bregje D.; Francke, Anneke L.; Verheij, Robert A.; Twisk, Jos W.R.; van Marum, Rob J.
Abstract: Background: Psychotropic drugs are frequently prescribed to people with dementia in nursing homes although severe adverse events and side effects are common. Less is known about the prevalence and types of psychotropic drug prescription in primary care for people with dementia. Objective: This study examined the prevalence of psychotropic drug prescriptions in primary care among persons with dementia from the year of diagnosis onwards. Methods: A longitudinal observational study using electronic health record (EHR) data was conducted. People with dementia were selected from EHR data of 451 general practices in the Netherlands. Age and gender‐adjusted psychotropic drug prescription rates were calculated per 1000 person‐years from the year the dementia diagnosis was first recorded in general practice up to 8 years after diagnosis. Results: Data of 15, 687 patients were analyzed. The prescription rate of psychotropic drugs (not including antidementia drugs) was 420 per 1000 person‐years (95% CI 409; 431) in the first year after the recorded dementia diagnosis, which increased to 801 per 1000 person‐years (95% CI 649; 989) in the eighth year. The most frequently prescribed drugs were antidepressants, antipsychotics, and antidementia drugs, followed by anxiolytics, hypnotics, and antiepileptics. Conclusions: After a dementia diagnosis is recorded in general practice, the prevalence of psychotropic drug prescriptions is substantial and increases steadily during the disease trajectory of persons with dementia. Although the (in)appropriateness of prescribing was not assessed, these insights may stimulate primary care clinicians to (re)consider their prescription policy of psychotropics for people with dementia more carefully.